Approaches to the Rational Design of Molecularly Imprinted Polymers Developed for the Selective Extraction or Detection of Antibiotics in Environmental and Food Samples. Issue 13 (9th July 2021) - Jamieson, Oliver; Mecozzi, Francesco; Crapnell, Robert D.; Battell, William; Hudson, Alexander; Novakovic, Katarina; Sachdeva, Ashwin; Canfarotta, Francesco; Herdes, Carmelo; Banks, Craig E.; Snyder, Helena; Peeters, Marloes
Abstract : Antimicrobial Resistance Antibiotics have revolutionized modern medicine and agriculture, but it is accepted that their use in veterinary or clinical practice exerts a selective pressure, which accelerates the emergence of antimicrobial resistance (AMR). This cover image illustrates numerous routes via which antibiotics can end up in the environment, highlighting the complexity of combatting AMR. More details can be found in article number 2100021 by Marloes Peeters and co‐workers.